MFAP4: a candidate biomarker for hepatic and pulmonary fibrosis? - Mölleken, Christian; Poschmann, Gereon; Bonella, Francesco; Costabel, Ulrich; Sitek, Barbara; Stühler, Kai; Meyer, Helmut E.; Schmiegel, Wolff H.; Marcussen, Niels; Helmer, Michael; Nielsen, Ole; Hansen, Søren; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background Several comparable mechanisms have been identified for hepatic and pulmonary fibrosis. The human microfibrillar associated glycoprotein 4 (MFAP4), produced by activated myofibroblasts, is a ubiquitous protein playing a potential role in extracellular matrix (ECM) turnover and was recently identified as biomarker for hepatic fibrosis in hepatitis C patients. The current study aimed to evaluate serum levels of MFAP4 in patients with pulmonary fibrosis in order to test its potential as biomarker in clinical practice. A further aim was to determine whether MFAP4 deficiency in mice affects the formation of pulmonary fibrosis in the bleomycin model of lung fibrosis. Methods 91 patients with idiopathic pulmonary fibrosis (IPF), 23 with hypersensitivity pneumonitis (HP) and 31 healthy subjects were studied. In the mouse model, C57BL/6 Mfap4+/+ and Mfap4-/- mice between 6‐8 weeks of age were studied. Serum levels of MFAP4 were measured by ELISA in patients and in mice. Surfactant protein D (SP-D) and LDH were measured as comparison biomarkers in patients with pulmonary fibrosis. Morphometric assessment and the Sircol kit were used to determine the amount of collagen in the lung tissue in the mouse model.Results Serum levels of MFAP4 were not elevated in lung fibrosis – neither in the patients with IPF or HP nor in the animal model. Furthermore no significant correlations with pulmonary function tests of IPF patients could be found for MFAP4. MFAP4 levels were increased in BAL of bleomycin treated mice with pulmonary fibrosis.Conclusions MFAP4 is not elevated in sera of patients with pulmonary fibrosis or bleomycin treated mice with pulmonary fibrosis. This may be due to different pathogenic mechanisms of liver and lung fibrogenesis. MFAP4 seems to be useful as serum biomarker for hepatic but not for lung fibrosis.